Distinguishing Causes of Neighborhood Racial Change: A Nearest-Neighbor Design - Bayer, Patrick; Casey, Marcus; McCartney, W. Ben; Orellana-Li, John; Zhang, Calvin (American Economic Review, 2025)
We study neighborhood choice using a novel research design that contrasts the move rate of homeowners who receive a new different-race neighbor immediately next-door versus slightly farther away on the same block. This approach isolates a component of preferences directly attributable to neighbors’ identities. Both Black and White homeowners are more likely to move after receiving a new different-race neighbor. Findings are robust to additional controls (e.g., income) and alternative research designs. We find evidence of heterogeneity in responses, especially associated with housing density, which has implications for understanding contemporary neighborhood racial change and prospects for maintaining stable, integrated neighborhoods. (JEL D91, J15, R23, R31)